Geography Teachers’ Perceptions of GeoAI Use in Learning: Persepsi Guru Geografi terhadap Pemanfaatan GeoAI dalam Pembelajaran - Purwa Priyana, Ekky; Somantri , Lili (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The integration of artificial intelligence in education, particularly GeoAI, represents a significant advancement in geography learning within the context of the Industrial Revolution 4.0. Specific Background: GeoAI combines geospatial technologies and artificial intelligence to support spatial analysis and interactive learning; however, its classroom utilization depends heavily on teachers’ perceptions and competencies. Knowledge Gap: Previous studies have emphasized artificial intelligence in general education, yet limited research specifically examines geography teachers’ perceptions of GeoAI utilization at the senior high school level. Aims: This study aims to analyze the levels of understanding, implementation, and reflection of geography teachers regarding GeoAI utilization in geography learning at public senior high schools in Coblong District, Bandung City. Results: The findings reveal that teachers’ understanding of GeoAI is uneven, implementation is generally adequate—primarily through Google Maps—and reflective ability is very strong in supporting learning processes. Novelty: This study provides a contextual analysis of teachers’ perceptions encompassing understanding, implementation, and reflection of GeoAI within geography education. Implications: The results highlight the need for strengthening conceptual understanding, digital competence, and geospatial literacy through training programs and policy support to advance GeoAI integration in geography learning. Highlights• Uneven conceptual mastery of GeoAI among geography teachers• Classroom practices dominated by accessible geospatial platforms• Strong reflective capacity supports technology-based learning development KeywordsGeoAI; Teacher Perception; Geography Learning; Digital Competence; Geospatial Literacy